Соціальне інвестування в контексті становлення соціального захисту населення - Колосок, Андрій Мирославович (Волинський національний університет імені Лесі Українки., 2019)
У статті розглянуто теоретичні та прикладні аспекти соціального захисту населення в Україні, визначено його специфіку та особливості формування. Досліджено еволюцію становлення поняття «соціальний захист», проаналізовано вітчизняні та зарубіжні визначення даної наукової категорії, сформовано власне бачення з позиції соціального інвестування. Обґрунтовано значимість соціального інвестування в контексті ефективного забезпечення соціального захисту населення. Розкрито сутність та складові соціальних інвестицій. Виокремлено основні проблеми соціального захисту населення, сформовано пріоритетні напрями його розвитку на загальнодержавному та регіональному рівні.
The purpose of the paper is to study the theoretical and applied principles of the state and prospects of the development of social investment in the context of the formation of social protection of the population in Ukraine. The article deals with the theoretical and applied aspects of social protection of the population in Ukraine, its specificity and peculiarities of formation are determined. The evolution of the concept of "social protection" has been investigated, domestic and foreign definitions of this scientific category have been analyzed, their own vision from the position of social investment has been formed. The importance of social investment in the context of effective provision of social protection of the population is substantiated. The essence and components of social investments are revealed. The main problems of social protection of the population are singled out, priority directions of its development are formed on the national and regional levels. Social protection of the population should take place within the framework of the state strategy of poverty reduction, which should violate the following priority directions of its development: the regulation of the legislative and regulatory framework, and the settlement of controversial provisions and the concentration of the whole array of regulatory provisions in one Social Code; improvement of the social assistance system, adherence to the principle of targeting social benefits with a gradual waiver of general privileges and subsidies; creation of conditions for selfdefense of citizens, that is, opportunities for employment with a decent wage reality; carry out an effective redistribution of funds from large businesses in favor of ordinary employees; provision of parity financing of the social protection program, creation of a long-term pension system, compulsory medical insurance, the role of local budgets and self-government bodies in social security, promotion of charitable programs, social-ethical marketing actions, and social responsibility of business.
Keywords: соціальне інвестування; соціальний захист; соціальні інвестиції; social investment; social protection; social investments; 364.3 (477.82)